Determinan Meningkatkan Kepuasan Kerja dan Dampaknya Pada Komitmen Organisasi - M. Thoyib; Mahdi Hendrik (Politeknik Negeri Sriwijaya, 2020)
The linkage of the five variables of training, career development, promotion, job satisfaction and commitment within the organization is paramount in achieving the goals of integrated organization. The success of the organization in achieving its goals beginning of the commitment between the owners and members of the organization, by empowering human resources through improvement and employee development and programmed regularly and provide compensation /remuneration in accordance with the developments and changes in the organization, so the impact on the employees and owner satisfaction organization (community).